STRATEGI PENGUATAN UMKM BERBASIS EDUKASI AKUNTANSI DAN PENGELOLAAN KEUANGAN MODERN DI DESA BANJARANYAR KECAMATAN SOKARAJA - Ainiyah, Ghonimah Zumroatun; Supriatin, Dyah; Ferika, Sania (Fokus ABDIMAS, 2025)
This community service activity aims to improve the ability of Micro, Small, and Medium Enterprises (MSMEs) to prepare simple financial reports as an effort to strengthen business management. Many MSMEs do not yet understand the importance of recording transactions and structured financial reports, making it difficult to assess their business performance. Through training and mentoring activities held in Banjaranyar Village, Sokaraja District, participants were trained to prepare profit and loss reports, balance sheets, and cash flow statements using simple methods. The results of the activity showed a significant increase in the participants' understanding and skills; most were able to separate personal and business finances and prepare independent financial reports. This activity has had a positive impact on the professionalism of MSME financial management and is expected to encourage sustainable economic growth in the community.Keywords: msmes, accounting education, modern financial management, financial literacy, economic empowerment